Religion and Politics in Burma - Smith, Donald Eugene (Princeton, NJ Princeton University Press, 2015)
The interaction of Buddhism and politics in the Theravada Buddhist countries since their independence is considered. Burmese attempts to relate Buddhism to the ideologies of nationalism, democracy, and socialism are analyzed.Originally published in 1965.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- -- PREFACE -- -- CONTENTS -- -- 1. BUDDHISM AND THE STATE IN OLD BURMA -- -- 2. RELIGIOUS POLICIES OF BRITISH RULE -- -- 3. BUDDHISM AND BURMESE NATIONALISM -- -- 4. RELIGION, IDEOLOGY, AND POLITICAL DEVELOPMENT -- -- 5. STATE PROMOTION OF BUDDHISM -- -- 6. THE SANGHA, POLITICS, AND REFORM -- -- 7. THE STATE RELIGION OF BURMA -- -- 8. REVOLUTION AND SECULARISM -- -- 9. DILEMMAS OF RELIGION AND POLITICS -- -- APPENDICES -- -- INDEX
Mode of access: Internet via World Wide Web.
In English
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Nationalism -- Burma; Buddhism and state -- Burma; Buddhism -- Burma; Nationalism -- Religious aspects -- Buddhism; Buddhism and state; Buddhism; Nationalism; RELIGION / Religion, Politics & State